An Overlooked Electrocardiogram Pattern: de Winter Pattern - Işık, Ömer; Ozkan, Ali Han (My University, 2024)
ABS TRACTElectrocardiogram (ECG) is an imaging tool used in the diagnosis of acute coronary syndrome. ST elevation is seen in total oc- clusion of the coronary artery. However, there are a number of high-risk ECG patterns that do not meet the criteria for ST-segment elevation my- ocardial infarction (STEMI) but are still suggestive of coronary artery occlusion. An ECG pattern called the de Winter patternis an ECG pattern that indicates severe occlusion of the proximal left anterior descending artery. In the de Winter pattern, there is an upward s loping ST segment at the J point that continues into long, positive symmetric T waves in the precordial leads. This ECG pattern is equivalent toa STEMI; therefore these patients should be triaged for emergency intervention. This case report describes a patient with this finding and reviews the current litera- ture.
Keywords: Acute coronary syndrome; coronary artery disease; Myocardial infarction; de Winter pattern